Prognostic value of serum NLR, PLR, P53, K67 level in lymph node metastasis of early gastric cancer - Long Xin; Shi Yingxi; Li Feifei; Wang Zhaojun; Wang Ying (Journal of Medical Biochemistry, 2025)
Background: To explore the predictive value of relevant detection indexes and pathological serum NLR, PLR, P53, and K67 levels in lymph node metastasis (LNM) in patients with early gastric cancer (EGC) after radical surgery. Methods: Clinical data of EGC patients (297 cases, all of whom underwent radical gastrectomy for gastric cancer) admitted to Sichuan Integrative Medicine Hospital from March 2019 to March 2024 were retrospectively included. The clinical data and pathological results were recorded and compared, and the related predictive factors were analysed. Results: There were 43 cases (14.48%) of postoperative LNM among the 297 EGC patients. The average number of lymph nodes detected in the LNM (-) group was 28.35 ± 8.23, which was lower than in the LNM (+) group (33 ± 15), *P* < 0.01. Binary multivariate logistic regression analysis identified the following as significant predictors of postoperative LNM in EGC patients: tumour size (OR: 2.582, 95% CI: 1.205-5.534), depth of invasion (OR: 2.953, 95% CI: 1.327-6.573), vascular invasion (OR: 2.724, 95% CI: 1.241-5.976), neuroaggression (OR: 2.681, 95% CI: 1.139-6.311), differentiation type (OR: 2.426, 95% CI: 1.140-5.119), and P53 (OR: 3.133, 95% CI: 1.183-8.301), P<0.05. The area under the ROC curve (AUC) for the model based on these indexes was 0.801. Compared with the LNM (-) group, the LNM (+) group had a lower overall survival rate at 1 and 2 years (P<0.05). Conclusions: Clinically relevant detection indexes and pathological P53 levels in patients after EGC radical surgery have a good predictive effect on the occurrence of LNM, which can assist in formulating scientific and reasonable clinical treatment plans.